Green`s function in free axisymmetric vibration analysis of annular thin plates with different boundary conditions - Żur, Krzysztof Kamil (Zielona Góra: Uniwersytet Zielonogórski)
Free vibration analysis of homogeneous and isotropic annular thin plates by using Green`s functions is considered. The formula of the influence function for uniform thin circular and annular plates is presented in closed-form. The limited independent solutions of differential Euler equation were expanded in the Neumann power series based on properties of integral equations. The analytical frequency equations as power series were obtained using the "method of successive approximations". The natural axisymmetric frequencies for singularities when the core radius approaches zero are calculated. The results are compared with selected results presented in the literature.
Keywords: annular plates; Green`s functions; singularities